Genetic Divergence for Grain Quality and Agromorphological Traits in Pearl Millet: GENETIC DIVERGENCE IN PEARL MILLET - Kavita; Dev vart; Ramesh Kumar; L. K. Chugh; R. N. Sheokand; Prakhar Singla (Annals of Arid Zone, 2024)
Calcium and magnesium deficiencies have severe health consequences in adults and children, especially in developing countries. Being naturally endowed with higher levels of grain minerals (Fe, Ca, Zn, Mg, P, and K), protein, carbohydrates, and fibre, pearl millet is considered as a potential crop to address micronutrient deficiency.  Fifty germplasm lines were assessed for genetic divergence using randomized block design during Kharif (Rainy) 2020 at CCSHAU, Hisar.  Observations were taken for eight quantitative characters, and grain Ca and Mg were determined for each genotype using ICP-MS.  D2 analysis and hierarchical cluster analysis utilising the UPGMA method were applied to ascertain the degree of diversification and relative proportion of each component trait towards the overall divergence. Both clustering approaches arranged genotypes into six clusters, signifying that there is of substantial genetic variation among 50 genotypes of pearl millet. Based on the ranking method used in D2 analysis, the grain Ca content displayed highest diversity, followed by grain yield per plant and dry fodder yield per plant. In both clustering methods, clusters with the genotypes HR-1038, HRI-115, and GP-227 had the highest mean performance for grain Ca and Mg content, whereas clusters with the genotypes HR-607, HR-101, HI-1012, HI-1013, and HTP03/13-927 had the lowest mean performance.  Regarding grains yield per plant, clusters containing the genotypes GP-141, GP-176, GP-181, EBL-12-237, and ICMR09888 performed exceptionally well.